2019
DOI: 10.22454/fammed.2019.229662
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Medical Student-Interpreter Collaboration in an Urban Free Clinic

Abstract: Background and Objectives: Cultural barriers and patient-provider language discordance exert deleterious effects on patient care. One solution has been the integration of medical interpreters into the care of patients with limited English proficiency. While medical schools and residency programs have started developing training programs on how to work with medical interpreters, no similar endeavor has been reported by student-run free clinics. Methods: Over 1 year, 76 third-year medical students (MS3s) were en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…This section is centrally relevant to the research aim of this study because it focuses on the use of interpreters during undergraduate medical/health care curricula. Interestingly, only five papers discussed the actual use of interpreters in medical or health care education as part of the curriculum [13,[18][19][20][21]. More specifically, Itaya et al 2009 [18] conducted a survey with students and faculty members to understand how the limited English patients (LEP) were managed in dental education and what was the perceived impact on the quality of education.…”
Section: Use Of Interpreters During Undergraduate Medical/health Care...mentioning
confidence: 99%
See 4 more Smart Citations
“…This section is centrally relevant to the research aim of this study because it focuses on the use of interpreters during undergraduate medical/health care curricula. Interestingly, only five papers discussed the actual use of interpreters in medical or health care education as part of the curriculum [13,[18][19][20][21]. More specifically, Itaya et al 2009 [18] conducted a survey with students and faculty members to understand how the limited English patients (LEP) were managed in dental education and what was the perceived impact on the quality of education.…”
Section: Use Of Interpreters During Undergraduate Medical/health Care...mentioning
confidence: 99%
“…Moreover, Kalet, Gany, and Senter's [22] and Kalet et al's [23] studies indicated that students greatly appreciated the training paradigms they used and expressed a strong interest in learning to collaborate with interpreters. In addition to the use of professional interpreters, two studies focused on the use of medical students as interpreters [21,34]. The results revealed that these students improved their skills and enhanced their cultural competency, but were challenged when attempting to separate the two roles in educational settings.…”
Section: Developing Students' Skills Through Training In How To Use I...mentioning
confidence: 99%
See 3 more Smart Citations